História da capoeira de rua de Belo Horizonte (1970-1990): manifestação cultural, lazer e política na sociedade moderna - Vinicius Thiago de Melo (2013)
The aim of this work was to analyze the Belo Horizontes Street Capoeira (1970-1990) in its transformation process, searched to reveal the history of its origin and its development during this period. The theme choice of this research occurred by my experience in the Belo Horizontes street wheels in Praça Sete square and Parque Municipal on the sundays, in the center of the city. This study was based from the complexity epistemology (MORIN, 1996) and cultural-historical theory (REY, 2004). The methodology of this research was developed from the method of verbal history. Six subjects, thats participated on this cultural process between 1970 and 1990 period, had been interviewed. This research was important for unmasked the capoeira historical process development in the Belo Horizontes city, what was few explorated by researchers. Thus, was make a description and interpretation of the motivations processes to teach, learning and training showed for subjects. The processes of organization and functioning of these street wheels was described too. Thats research concluded that Street Capoeira was a organization model that had a great expression during the 1970 and 1980 decade, being structuralized basically from the local interactions between the subjects. That historic process, was possible to observe some discontinuities provoke for a leisure institutionalizing process, which had provided the Capoeiras Groups model emerge. This investigation demonstrated that historical discontinuities was strongly influenced by the trends globalizes of the modern society (GIDDENS, 2002). In this manner, was make a critical to the model of the Capoeiras Groups - Angola, Regional and Contemporary - for the description and interpretation of the processes which made possible its emergency and consolidation, as well as the implications thats hegemony model can produce in relation to the other possibilities to organized this activity.